Peningkatan perekonomian masyarakat melalui pelatihan ecoprint pada Ibu-Ibu PKK di Desa Jetis, Kecamatan Bandungan, Kabupaten Semarang - Cahyanti, Divania Nur Indah; Ikhrimah, Jihan Fara; Wardhani, Nava Puspa; Fitriyani, Rizka (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
The improvement in the community's economy can be seen from the environmental aspect, where every citizen can take advantage of the natural potential around them. Ecoprint is one of the business opportunities that can be implemented by the community, especially residents of Jetis Village in Bandungan District, where Bandungan is the area that produces the most flowers or ornamental plants, and this is able to help the community make ecoprints. The purpose of this journal or article is to serve as a main step in bridging the Jetis Village community with the wider community and even large entrepreneurs who can look at the business potential that exists there. Using the lecture method, Ecoprint was first socialized to target PKK women representing all hamlets in Jetis Village with the aim of obtaining clear information about the purpose, objectives and method of making this ecoprint and then continued with the practice of making ecoprints. This socialization was held to increase the knowledge and skills of Jetis Village PKK mothers in making ecoprint batik on cloth media.